Malaria and Macronutrient Deficiency as Correlates of Anemia in Young Children: A Systematic Review of Observational Studies - Sarah McCuskee (Ubiquity Press, 2015)
Background: Anemia is a leading cause of pediatric mortality and impaired development and is highly prevalent in young children in sub-Saharan Africa. Populations most affected by anemia also often are at high risk for malaria and macronutrient deficiency, conditions that may exacerbate anemia. Due to its multifactorial etiology, anemia presents a significant global health challenge, and successful interventions targeting anemia require a greater understanding of the relative and interacting contributions of malaria and undernutrition. Objectives: The aim of this study was to assess the associations of malaria and undernutrition, indicated by stunting and wasting, with anemia in young children using a systematic review of observational studies. Methods: Searches were conducted in MEDLINE and Scopus. Articles were screened and reviewed for inclusion by two reviewers. Studies published after 1990 that measured anemia, 'Plasmodium' falciparum malaria, and stunting or wasting in children aged 5 years or under were included. Findings: Of 620 articles reviewed, 15 studies from 9 countries in sub-Saharan Africa were included. Statistical approaches and anemia measurement varied widely, so synthesis was qualitative. Thirteen studies found that malaria infection was associated with anemia or lowered hemoglobin; in these studies, malaria accounted for more of the variation in anemia than nutritional status. In contrast, only 7 of the 13 studies investigating stunting and 3 of the 6 studies investigating wasting as correlates of anemia observed statistically significant associations at α = 0.05. The role of nutrition in anemia may differ by country. Conclusions: Observational epidemiologic studies consistently demonstrate that malaria is an important correlate of anemia in young children; however, the roles of stunting and wasting and interactions between malaria and nutrition require further investigation. Based on the current evidence, these findings suggest that global health strategies to reduce the burden of anemia should prioritize malaria prevention and support research on alternative causes of anemia that reflect local conditions.